ANEMIA PREVALENCE IN RHEUMATOID ARTHRITIS IN 1979 AND 1999 - Yu. V. Mouraviev; V. V. Lebedeva; K N Kashnicova; E A Galushko (Научно-практическая ревматология, 2002)
Objective. To assess anemia prevalence in RA pts in 1979 and 1999 years. Material. Retrospective analysis of 327 case reports from RA pts admitted in the clinical department of Instituteof Rheumatology of RAMS for the first quarter of 1979 (n=115) and first quarter of 1999 (n=212) was done.Criteria for anemia were the falling of hemoglobin level lower than 120 g/1 for women and 130 g/1 for men.Results. In 1999 anemia prevalence in RA pts as compared with 1979 was doubled which to some extend depended on the activity of inflammatory process.Conclusion. It seems, that in the development of anemia in RA other factors beside inflammation take place, in particular therapy because ESR rise not always effected the prevalence of anemia in RA pts.